Biomechanical factors of effective Seoi-Nage in judo - Ishii, T.; Ae, M. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
The purpose of this study was to compare the seoi-nage techniques between the elite and non-elite judo athletes. The information obtained helps to increase our knowledge on biomechanical factors to determine the effectiveness of seoi-nage. The motion data of the seoi-nage were collected on three male elite judo athletes and seven male student athletes using a three-dimensional motion analysis technique. The velocity generated by the hikite and hip were greater and the angles of pulling and hitting were smaller in the elite judo athletes than the student judo athletes. The comparison of the effects of the velocity and angles of pulling and hitting on the generation of the angular momentum of uke implied that these variables could be indices for coaches to evaluate the effectiveness of the seoi-nage.